The Role of the Islah Movement in the State’s Constitution of Perlis, Malaysia - Abd Hamid, Mohd Nasir; Ismail, Che Latifah; Jusoff, Kamaruzaman (2009)
In 19th Century CE the term is· la _ h· is used to denote ‘reform’ to perceive idealism of reformers, al-Afgha _ ni _ , ‘Abduh and Rida and those who were influenced by them. They struggled to refine Muslim society and to call them back to Islam. The objective of this paper is to study factors of diffusion of the idealism in Perlis, Malaysia. Besides, it would indicate the role of the is· la _ h· movement in determining the notion of Perlis’s Constitution. Through researches in many documents as well as interviews the study found that the movement in Perlis emerged in the early 1920s CE to challenge the practice of the Sha _ fi‘i _ madhhab (school of thought) in the state. The movement succeeded in challenging the strength of Kaum Tua (the Shafi’i adherents) and caused the closing of their pondok (learning centre). What was more important, the movement’s proposal to establish the doctrines of ahl al-sunnah wa-’l-jama _ ‘ah without being subject to any particular madhhab to be the basis of the State's structures gained the support of the Perlis Sovereign as well as the State Executive. Meanwhile, a King who would be appointed to govern the State should be a person who follows the doctrines. When compared with provisions of the other States in Malaysia it means that only Perlis has chosen to make an open rejection to the practice of taqli _ d of particular madhhab in the State’s religious administration. Therefore, it would be good to suggest that people should be given a wide opportunity to study, to accept and to practise any opinion that is in accordance with al-Qur’a _ n and al-Sunnah in order to show a great appreciation of the State’s doctrine.